2022
DOI: 10.1093/ofid/ofac690
|View full text |Cite
|
Sign up to set email alerts
|

Which Curve Are We Flattening? The Disproportionate Impact of COVID-19 Among Economically Marginalized Communities in Ontario, Canada, Was Unchanged From Wild-Type to Omicron

Abstract: Person-level surveillance (n = 14 million) and neighbourhood-level income data were used to explore magnitude of inequalities in COVID-19 hospitalizations and deaths over five waves in Ontario, Canada. Despite attempts at equity-informed policies alongside fluctuating levels of public health measures, the magnitude of inequalities in hospitalizations and deaths remained unchanged across waves.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Cumulative covid-19 related deaths per capita by neighbourhood income in Ontario, Canada (population 14 million) across seven waves of the pandemic. Neighbourhood level income accounts for household size and is adjusted for city level cost of living9…”
Section: Lessons From the Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Cumulative covid-19 related deaths per capita by neighbourhood income in Ontario, Canada (population 14 million) across seven waves of the pandemic. Neighbourhood level income accounts for household size and is adjusted for city level cost of living9…”
Section: Lessons From the Pandemicmentioning
confidence: 99%
“…8 In Canada's most populous province, Ontario, the income gap in covid-19 outcomes has not improved over time (fig 1). 9 Rates of covid-19 hospital admissions and deaths remained threefold higher in the lowest income neighbourhoods compared with highest income areas in each pandemic wave, despite the province eventually achieving "equality" in two dose vaccine coverage and usual measures of hybrid protection (known infection and vaccination) across income. 9 We examine the ways in which research may have contributed to homogenising public health responses to a heterogeneous epidemic and how research could have been used to shape more tailored health policies and implementation efforts.…”
Section: Lessons From the Pandemicmentioning
confidence: 99%
“…Social inequalities in COVID-19 deaths were evident during the early pandemic period across the world(28). Data are emerging to suggest social inequalities in COVID-19 deaths might have persisted into later pandemic waves in the UK(9), the US(10) and Canada(11). However, these studies were limited by their ecological design(10,11) and/or inability to account for potential confounders including comorbidities(9,11).…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, there is limited research on the role of social and demographic factors that may influence both the incidence and within province spread of Mpox (2, 9). This is an important area of study considering prior work conducted in Ontario in the context of similar diseases like Covid-19, where researchers found that people that are marginalized had increased risk of COVID-19 morbidity and mortality as compared to the general population in Ontario (1214). This may demonstrate possible lack of health service equity (15).…”
Section: Introductionmentioning
confidence: 99%